CUSTOMER REVISIT DECISION AND SATISFACTION AS A CONSEQUENCE OF MARKETING MIX AND SERVICE QUALITY - Serli Pabara; Muammar Khaddapi; Antong; Syafruddin (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
The tight competition for hotels means that hotels need to implement marketing mix strategies and service quality so that they can provide satisfaction to hotel consumers and increase their decision to visit again. The aim of this research is to determine the influence of the marketing mix and service quality on consumers’ revisit decisions through consumer satisfaction as an intervening variable. The method approach used in this research is a quantitative method. Data collection was used by distributing questionnaires to respondents with a total of 100 respondents, using the margin of error (MoE) formula in determining the number of respondents. The data that has been collected will be subjected to descriptive and verification analysis using the SmartPLS statistical tool. The SmartPLS test results show that the marketing mix directly has a positive and significant effect on consumer satisfaction and the decision to revisit. Meanwhile, indirectly the marketing mix has a positive and significant effect on the decision to revisit through consumer satisfaction. Service quality directly has a positive and significant effect on consumer satisfaction, but has a positive but not significant effect on the decision to revisit. Indirectly, service quality has a positive and significant effect on the decision to revisit through consumer satisfaction. Consumer satisfaction has a positive but not significant effect on the decision to revisit hotel consumers. Implementing an integrated marketing strategy and improving service quality can significantly increase consumer satisfaction, which in turn can increase customer loyalty and hotel profitability. In addition, this research can enrich academic literature and provide a basis for further research in the field of marketing and service management.